Evaluation of DMIT [4,5-Dimercapto-1,3-Dithyol-2-Thionate] as chelating agent in a cloud point extraction procedure for Pb2+ determination in water samples - doi: 10.4025/actascitechnol.v35i2.18076 - Naiara Vieira Godoy; Bruna Fabrin Somera; Wagner José Barreto; Sônia Giancoli Barreto; Cesar Ricardo Teixeira Tarley (Acta Scientiarum: Technology, 2013)
The present study proposes a new method for cloud point preconcentration of Pb2+ ions based on complex formed with [4,5-dimercapto-1,3-dithyol-2-thionate] and posterior determination by flame atomic absorption spectrometry (FAAS). The preconcentration of Pb2+ was carried at pH 5.0 under following conditions: time and temperature of batch at 15 min. and 70oC, respectively, 0.1% (v/v) Triton X-114, 0.003 mol L-1 acetate/acetic acid buffer solution, 1.0 x 10-5 mol L-1 DMIT and 0.5% (m/v) NaCl. Under the best analytical conditions the method provided a limit of detection of 2.85 mg L-1 by preconcentrating 10.0 mL of sample and calibration curve ranging from 0 up to 650 mg L-1 (r = 0.99945). The applicability of proposed method for Pb2+ determination in natural waters without interferences was checked through addition/recovery tests.